Oxide tribolayer effects on fretting wear of steel under variable displacement amplitude - Roderick Jacques; Abdeljalil Jourani; Salima Bouvier; Yan-Ming Chen (Results in Engineering)
Most of the studies in the literature dealing with fretting have focused on wear mechanisms without considering the formation of oxide layers, whose nature can vary depending on the displacement amplitude and the material pairing. This omission limits the understanding of how different fretting conditions influence surface transformations and ultimately affect wear behavior. This study investigates the wear mechanisms and oxide layer formation in two steel-steel tribosystems, 100Cr6/100Cr6 and 20MnCr5/100Cr6. A parametric approach was adopted, varying displacement amplitudes from 20 to 200 µm under a constant normal load of 10 N, to elucidate the roles of the third body, oxidation, and debris ejection on fretting wear. Friction behavior and electrical contact resistance were monitored in real-time to assess the evolution of contact conditions. Surface characterization was conducted using SEM, Energy dispersive X-ray (EDX), FIB-TEM, and Transmission Kikuchi diffraction (TKD) to analyze wear morphologies and oxide layer composition. The results reveal that although both material pairs developed oxide-based tribolayers at increased amplitudes, only the 20MnCr5/100Cr6 pair exhibited a notable reduction in wear volume between amplitudes of 50 µm and 100 µm. This reduction was attributed to the formation of a more effective third-body layer. Furthermore, TKD analysis demonstrated that magnetite-rich oxide layers formed at 50 µm displacement amplitude in the 100Cr6/100Cr6 pair were more compact and protective compared to the hematite-dominated layers observed at higher amplitudes. These findings underscore the critical influence of material pairing and displacement amplitude on the stability and protective effectiveness of oxide layers in fretting conditions.